The effect of BEMER therapy on selected blood indicators in the process of biological restitution after exercise endurance. A case study - Mirosław Mrozkowiak; Mariusz Posłuszny (Journal of Education, Health and Sport, 2017)
Introduction. Microcirculation vessels comprise 99% of blood vessels in an adult human body11. Capillary network density in particular tissues grows proportionally to their oxygen demand. BEMER therapy, used as complex or supplementary treatment, improves basic physiological processes, angiokinesis, microcirculation, as well as oxygenation and nutrition of muscle cells. Due to particular biorythmic modulation, it exerts synergic influence on primary and secondary, slightly bigger, blood vessels.